Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Petrokopindo Cipta Selaras Gresik - Apriyana Nur Kharisma; Nur Cahyadi (Universitas 45 Surabaya, 2023)
The rapid development of the era in the era of globalization has made companies including small companies and large companies compete with each other to maintain their business. In this case, companies need potential resources, both leaders and employees, for tasks that determine the achievement of goals. Human resources owned by companies must also have good quality performance. Quantitative research methods were used in this study, researchers collected data through respondents using a questionnaire. The population of this study are employees of PT. Petrokopindo Cipta Selaras. Total employees of PT. Petrokopindo Cipta Selaras, namely 178 people, while the number of samples in this study was 123 people. The results of the research show that Employee Performance (Y) at PT. Petrokopindo Cipta Selaras is partially influenced by Work Motivation Variables (X1), Work Environment (X2) and Work Discipline (X3)